Kinerja Sapi Bali Jantan yang diberikan pakan Rumput Gajah (Punnisetum purpureum) subtitusi fermentasi Jerami Padi - Alimuddin Alimuddin; M. Jen Wajo; Marlyn N Lekitoo (Program Pascasarjana Universitas Papua, 2018)
The research was aimed to study Bali bulls fed with Pennisetum purpureum with fermented rice straws substitution in Manokwari Regency, West Papua was conducted experimentally with 12 Bali bulls that have average weight of 176.02±38.35 kg with 2 – 2,5 years old for 5 months duration. The study was designed using complete randomized design of nested pattern with 3 (three) treatments, 4 (four) replications and 4 (four) times weighing, with an assumption that Bali bulls are nested during weighing time. The results of this study showed that Penicetum purpureum substitution with fermented straws did not significant on Bali bulls body weight. The duration of fermented rice straws feeding that substituted with Penicetum purpureum significant for Bali bulls weight gain with the average absolute weight gain is 0,68 kg/ day, as well as relative body weight gain of 0,033 kg/ day. The potential of rice straws in Manokwari Regency might be utilized as Bali bulls feed as many 9.431 – 46.846 cattle.